PENINGKATAN HASIL BELAJAR MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW - Maria Foustina Perada Lalu; Theresia Laurens; La Moma (Science Map Journal, 2022)
This research is motivated by the learning results of learners on the material of building flat side space that is still low. This research was conducted to improve learners' learning outcomes on flat-sided room building materials through jigsaw-type cooperative learning models in class VIII SMP Negeri 9 Kei Kecil. This type of research is a class action study (PTK) consisting of two cycles with each cycle consisting of two meetings. The subjects in this study were class VIII learners with a sample of 15 learners. The data collection techniques in this study are observations and tests. Cycle I results in as much as 60% of learners reach KKM and do not meet the classic completion of 65%. The results of cycle II showed an increase of 86.67% of learners reaching KKM and fulfilling classical completion of 65%. Based on the results obtained, it can be concluded that using a jigsaw-type cooperative learning model can improve the learning outcomes of students of class VIII of SMP Negeri 9 Kei Kecil